3D FEM Analysis of Pounding Response of Bridge Structures at a Canyon Site to Spatially Varying Ground Motions. Issue 4 (April 2013) - Bi, Kaiming; Hao, Hong; Chouw, Nawawi
Previous studies of pounding responses of adjacent bridge structures under seismic excitation were usually based on the simplified lumped mass model or beam-column element model. Consequently, only 1D point to point pounding, which is usually in the longitudinal direction of the bridge, could be considered. In reality, pounding could occur along the entire surfaces of the adjacent bridge structures. Moreover, spatially varying transverse ground motions generate torsional responses of bridge decks and these responses may cause eccentric poundings. That is why many pounding damages occurred at corners of the adjacent decks as observed in almost all previous major earthquakes. A simplified 1D model cannot capture torsional response and eccentric poundings. To more realistically investigate pounding between adjacent bridge structures, a two-span simply-supported bridge structure located at a canyon site is established with a detailed 3D finite element model in the present study. Spatially varying ground motions in the longitudinal, transverse and vertical directions at the bridge supports are stochastically simulated as inputs in the analysis. The pounding responses of the bridge structure under multi-component spatially varying ground motions are investigated in detail by using the finite element code LS-DYNA. Numerical results show that the detailed 3D finite element model clearly captures the eccentric poundings of bridge decks, which may induce local damage around the corners of bridge decks. It demonstrates the necessity of detailed 3D modelling for a more realistic simulation of pounding responses of adjacent bridge decks to earthquake excitations.